2017
DOI: 10.3389/fnins.2016.00613
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Promotes Remyelination after Cuprizone Treatment by Enhancing Myelin Debris Clearance

Abstract: Promoting remyelination is crucial for patients with demyelinating diseases including multiple sclerosis. However, it is still a circuitous conundrum finding a practical remyelinating therapy. Electroacupuncture (EA), originating from traditional Chinese medicine (TCM), has been widely used to treat CNS diseases all over the world, but the role of EA in demyelinating diseases is barely known. In this study, we examined the remyelinating properties and mechanisms of EA in cuprizone-induced demyelinating model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…LIF was previously reported by us and others to protect OPCs and oligodendrocytes from inflammation-induced cell death (32)(33)(34)(35). At the site of OSM overexpression higher levels of neurotrophic factor CNTF, proinflammatory (CD86 and IL1Ī²), and antiinflammatory (CD32 and CD206) mediators were detected, all known to promote remyelination (36)(37)(38)(39)). Yet, TIMP-1 was the only factor both reduced in the absence of OSMRĪ² and increased upon LV-OSM treatment.…”
Section: Discussionmentioning
confidence: 66%
“…LIF was previously reported by us and others to protect OPCs and oligodendrocytes from inflammation-induced cell death (32)(33)(34)(35). At the site of OSM overexpression higher levels of neurotrophic factor CNTF, proinflammatory (CD86 and IL1Ī²), and antiinflammatory (CD32 and CD206) mediators were detected, all known to promote remyelination (36)(37)(38)(39)). Yet, TIMP-1 was the only factor both reduced in the absence of OSMRĪ² and increased upon LV-OSM treatment.…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, lipid-associated myelin debris (shown by Oil Red O staining) decreased following electroacupuncture, which corresponds with the accumulation of microglia. Consistent with these results, our previous research showed that electroacupuncture was an efficient therapeutic intervention to modulate microglial function [15]. Myelin debris are pathological products that accumulate in lesion areas during cuprizone treatment and the process of demyelination in MS patients; moreover, they are potent obstacles for remyelination as well as for axon regeneration [23].…”
Section: Discussionmentioning
confidence: 57%
“…Various acupoint-based treatments are used in scalp electric acupuncture (for example, Baihui [GV20]). This improves neurological function scores via cell proliferation and differentiation [ 14 , 17 , 40 , 41 , 42 ]. Transcranial direct current stimulation (tDCS) induces neurogenesis, independently of polarity and cathodal tDCS-recruited oligodendrocyte precursors, toward the lesion in a rat focal cerebral ischemic model [ 43 ].…”
Section: Discussionmentioning
confidence: 99%